Passively Q-switched erbium doped fiber laser based on graphene and carbon nanotube saturable absorbers - Mahroof Mohamed Mafroos; Husni Hani Jameela Sapingi; Azura Hamzah (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
A passively Q-switched erbium-doped fiber laser (EDFL) was experimented on by employing graphene, single walled carbon nanotubes (SWCNT) and multi-walled carbon nanotube (MWCNT) saturable absorbers (SA). The SA film was obtained by embedding the graphene, SWCNT and MWCNT into polyvinyl alcohol (PVA). The graphene SA was prepared by dipping a PVA thin film into the graphene solution while carbon nanotubes SAs were prepared using the casting method and placed in the ring cavity to produce a stable pulse laser. Graphene, SWCNT and MWCNT SAs were operating at wavelengths of 1558.92 nm, 1557.98 nm and 1558.51 nm, respectively, whereas the continuous wave was 1560.72 nm at the input pump power of 56 mW. The pulse energy, output power, repetition rate and pulse width were compared in graphene, SWCNT and MWCNT SAs. The shortest pulse width retrieved in graphene, SWCNT and MWCNT were 3.90 µs, 3.62 µs 4.43 µs and produced at the repetition rate of 115.00 kHz, 130.70 kHz, and 89.13 kHz, respectively. In comparison to graphene and SWCNT SAs, MWCNT SAs exhibit the best performance in terms of output power of 2.19 mW and high pulse energy of 24.57 nJ in passively Q-switched EDFL.